A Literary Testimonial to Banal Evil: Dehumanization in The Narrative of Arthur Gordon Pym - Daniela Cârstea (European Journal of American Studies)
The problematics of trauma and testimony are perforce in a closely-knit relation with the issue of evil, in particular with the strand of evil that made possible the concentration camps in Auschwitz. Edgar Allan Poe’s Narrative of Arthur Gordon Pym will be considered as primarily an event of speech, and its testimony as a mode of truth’s realization beyond what is available as statement. What emerges from the comments on Pym, from the explication of some of the death scenes, from the gratuitousness of the violence, and the nonchalance of Pym’s report, is not the horror, but a sense of the casualness of death, the “banality of evil” that Poe opposes to the “grandeur of evil,” looking ahead to Auschwitz and the Gulag. In Pym, Poe presents us with a rare instantiation of pure (and banal) evil in the casually-reported scene of the cannibalization. I intend to supplement the philosophical response to the question of (banal) evil provided by Hannah Arendt and Giorgio Agamben by a psychoanalytical one, with a footing in the signature terminology of Melanie Klein.